Development of Powerpoint-Based Explainer Video Learning Media on Ecosystem Material - Muhammad Salamun Ahsan; Maslikhah Maslikhah (FKIP - Universitas Riau, 2026)
This study aimed to develop and examine the effectiveness of a PowerPoint-based explainer video learning medium for ecosystem topics in Grade V of Madrasah Ibtidaiyah. The research employed a Research and Development (R&D) approach using the ADDIE model, involving analysis, design, development, implementation, and evaluation. The product was validated by material and media experts and then tested with fifth-grade students at MI Al Ikhlas and MI Al Ma’arif. Data were collected through questionnaires, observations, and pre-test–post-test results. The findings indicate that the developed media was rated as very feasible by both experts and users. Students who learned using the explainer video showed higher learning outcomes and better engagement compared to conventional learning. The integration of visual explanation, narration, and PowerPoint slides helped students better understand ecosystem concepts. This study contributes to the development of interactive digital learning media in elementary science education by providing an effective and practical alternative for improving students’ learning outcomes.